The implementación of co-teaching to the technical and technological english course at the sena (2021)
Labor competitiveness in our country increasingly demands that new workers must have different skills to complement their professional profile and achieve a better performance in the provision of work; the ability to communicate in English is essential to complete a suitable professional profile and increases the possibilities of being hired and keeping a job. Due to this, the Servicio Nacional de Aprendizaje (SENA), which is the institute responsible for offering the majority of technical and technological training in our country, includes in the curriculum of its programs different compulsory English courses to obtain the degree. The participants of the Intervention Project are learners from different areas of training: commerce and finance, industry, computer science, design, as well as the work group that will accompany them to strengthen language skills in L2 and reach to the English corresponding levels of English needed by learners, A2 for technical programs and B1 for technologists, the practitioners were three students of the degree in bilingualism of Universidad Tecnológica de Pereira. This academic accompaniment focuses on the application of the methodologies of co-planning and co-teaching as well as the creation of content for the teaching of English with a specific purpose among facilitators of the Servicio Nacional de Aprendizaje (SENA) and Universidad Tecnológica de Pereira (UTP). Also, through tutoring sessions, English events such as Semana de los Idiomas or Bootcamps, and conversation clubs. During this process, teamwork with the apprentices was accomplished and strategies to facilitate the acquisition of new linguistic resources were given satisfactorily, this was evidenced when the apprentices showed an improvement in the English lessons, minimizing the gaps that they have at the beginning and increasing the fluency and the participation when talking in English. Finally, this pedagogical accompaniment provided the students with different alternatives to improve their L2 (English) through the agreement made by SENA institutions and the UTP.